A Framework for Macroprudential Bank Solvency Stress Testing : Application to S-25 and Other G-20 Country FSAPs - Jobst, Andreas A. (IMF Working Papers; Working Paper ;, 2013)
The global financial crisis has placed the spotlight squarely on bank stress tests. Stress tests conducted in the lead-up to the crisis, including those by IMF staff, were not always able to identify the right risks and vulnerabilities. Since then, IMF staff has developed more robust stress testing methods and models and adopted a more coherent and consistent approach. This paper articulates the solvency stress testing framework that is being applied in the IMF's surveillance of member countries' banking systems, and discusses examples of its actual implementation in FSAPs to 18 countries which are in the group comprising the 25 most systemically important financial systems ('S-25') plus other G-20 countries. In doing so, the paper also offers useful guidance for readers seeking to develop their own stress testing frameworks and country authorities preparing for FSAPs. A detailed Stress Test Matrix (STeM) comparing the stress test parameters applie in each of these major country FSAPs is provided, together with our stress test output templates.